The determinants of European agricultural trade interference - Egbert Gerken (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1986)
First World politicians ascribe an exceptionally high social value to the well-being of domestic farmers, apparently without being penalized by political setbacks. In the European Community (EC) , they fix domestic prices on most agricultural commodities above world market prices, sustain these prices through variable import levies and export restitutions, subsidize production and factor use and dampen price fluctuations, all with the purpose of raising the levels and improving the stability of farmers1 incomes. While agricultural policymakers in the United States (US) and in most other OECD countries do not always intervene in the same commodity markets, they generally rely on the same set of instruments . Given the fairly inelastic demand and supply responses among Second World planners and the limited flexibility among Third World producers and consumers, the effect of agricultural policies adopted in the First World is to lower the levels of world agricultural prices and to amplify their oscillations . World welfare' is reduced as a result.
Keywords: 330; Agrarpolitik; Agrarmarkt; Agraraußenhandel; Agrareinkommen; EU-Staaten